Pengaruh Berbagi Pengetahuan, Organizational, Dan Disiplin Kerja Terhadap Prestasi Kerja - Haenilah, Tasya; Mardhiyah, Ainun; Siregar, Onan Marakali (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze how knowledge sharing, organization, and work discipline influence work performance among employees at Bank Sumut Medan Imam Bonjol. The influence of knowledge sharing, organization, and work discipline will be analyzed both partially and simultaneously on work performance. The form of research used in this study is quantitative research with an associative approach. The population in this study comprises all employees at the PT Bank Sumut Medan Imam Bonjol office, totaling 33 people, with sampling techniques using saturated sampling. Primary data used in this study were obtained by distributing questionnaires directly, while secondary data were obtained through literature studies. The data analysis methods used are instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results showed that knowledge sharing, organization, and work discipline had a positive and significant effect both partially and simultaneously on work performance at PT Bank Sumut Medan Imam Bonjol. The correlation coefficient (R) value is 0.943, which means that there is a relationship between the variables of Knowledge Sharing (X1), Organization (X2), and Work Discipline (X3) on Work Performance (Y) of 94.3%, indicating a very close relationship between these variables. The Adjusted R Square value of 0.878, or the coefficient of determination, shows that the variables of Knowledge Sharing (X1), Organization (X2), and Work Discipline (X3) explain 87.8% of the variation in Work Performance (Y), while the remaining 12.2% is influenced by other factors outside this research model.